Skrining Thalassemia pada remaja di Desa Tanjung Pering Kecamatan Indralaya Ogan Ilir A PADA REMAJA DI DESA TANJUNG PERING KECAMATAN INDRALAYA OGAN ILIR - Dewi Rosariah Ayu; Dian Puspita Sari (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Indonesia is a country that has a Thalassemia carrier population of around 3-8%, even in some areas reaching 10%. Thalassemia is difficult to detect because it is asymptomatic, so the role of screening as early detection is needed. Thalassemia screening is needed to prevent and break the chain of this blood disorder. The purpose of this community service is to increase awareness and understanding the symptoms and management of thalassemia in Tanjung Pering Village, especially the students of SMAN 1 Indralaya Utara. As many as 51 students take part during counseling and laboratory examination. of blood. Based on screening result, 9 of them (17.6%) were suspected of being carriers of Thalassemia. Early detection of thalassemia is very important to break the chain of this disease in the next generation.